Identitas dalam Kristus sebagai Fondasi Transformasi Sikap Hidup dan Keteladanan Umat - John Christ Dwiaprianto A; Yanto Paulus Hermanto; Victor Deak (Sekolah Tinggi Alkitab Jember, 2026)
True Christian identity is the foundation that determines the direction of life and witness of believers. Since its mention in Antioch (Acts 11:26), the term